2021
DOI: 10.1038/s41598-020-79948-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of PAI-1 in hepatic steatosis and dyslipidemia

Abstract: Plasminogen activator inhibitor 1 (PAI-1) is a functional biomarker of the metabolic syndrome. Previous studies have demonstrated that PAI-1 is a mechanistic contributor to several elements of the syndrome, including obesity, hypertension and insulin resistance. Here we show that PAI-1 is also a critical regulator of hepatic lipid metabolism. RNA sequencing revealed that PAI-1 directly regulates the transcriptional expression of numerous genes involved in mammalian lipid homeostasis, including PCSK9 and FGF21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 41 publications
1
48
0
1
Order By: Relevance
“…Disruption of PCSK9-LDLR interaction is still compatible with downstream signaling effects, as the antibody-antigen complex may still clear the circulation and enter the liver via LDLR-independent target-mediated mechanisms. For example, we have shown that plasma PAI-1 levels decrease following PCSK9 blockade, an effect that most probably is independent of LDLR ( 47 ). However, no metabolic effects of the increased plasma PCSK9 levels induced by PCSK9i therapy have been thus far identified, although we can speculate that situations leading to dissociation of the antigen from the therapeutic antibody would likely trigger an increase in cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of PCSK9-LDLR interaction is still compatible with downstream signaling effects, as the antibody-antigen complex may still clear the circulation and enter the liver via LDLR-independent target-mediated mechanisms. For example, we have shown that plasma PAI-1 levels decrease following PCSK9 blockade, an effect that most probably is independent of LDLR ( 47 ). However, no metabolic effects of the increased plasma PCSK9 levels induced by PCSK9i therapy have been thus far identified, although we can speculate that situations leading to dissociation of the antigen from the therapeutic antibody would likely trigger an increase in cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Using cultured adipocytes from PAI-1+/+ and PAI-1-/mice, the deletion of PAI-1 in adipocytes ameliorated insulin resistance by promoting glucose uptake and adipocyte differentiation [36]. Inhibition of plasma PAI-1 activity also resulted in improved hyperlipidemia in a diet-induced obese mouse model [37]. In mouse models, pharmacological inhibition of PAI-1 prevented hepatic steatosis and reduced serum cholesterol level by reducing PCSK9 synthesis [37].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Finally, changes in these non-traditional biomarkers may be not only due to improvement in weight loss, physical fitness, and physical activity, but also due to changes in traditional risk factors. This finding is not surprising given these factors have also been associated with hypertension ( 49 ), dyslipidemia ( 50 ), and diabetes ( 51 , 52 ). Despite these study limitations, we believe our study provides important information on how an exercise program administered in a real-world setting can improve non-traditional markers of cardiovascular risk.…”
Section: Limitationsmentioning
confidence: 88%